Tectonic links between Proterozoic sedimentary cycles, basin formation and magmatism in the Albany–Fraser Orogen, Western Australia - Spaggiari, C.V.; Kirkland, Chris; Smithies, R.; Wingate, M. (Geological Survey of Western Australia, 2014)
Preserved in the Albany–Fraser Orogen are the remnants of two, regionally extensive basin systems — the c. 1815 to 1600 Ma Barren Basin and the c. 1600 to 1305 Ma Arid Basin. An extensive U–Pb zircon geochronology dataset is used to demonstrate that the two regional basins record two cycles of sedimentation related to major tectonic events in the Albany–Fraser Orogen. The first cycle (Cycle 1) filled the Barren Basin with dominantly Neoarchean zircon detritus derived from the Archean Yilgarn Craton. Coeval voluminous, dominantly felsic magmatism modified the southern and southeastern Yilgarn Craton crust from 1815 to 1800 Ma, 1780 to 1760 Ma, and during the 1710–1650 Ma Biranup Orogeny, providing a second important detrital zircon source into the Barren Basin. The abundance of locally derived sediment deposited onto a reworked Archean Yilgarn Craton substrate indicates a largely extensional tectonic setting, consistent with a broad continental rift basin or alternatively, a long-lived back-arc basin system along the craton margin. However, if the Barren Basin formed in a back-arc setting, the associated subduction zone and magmatic arc must have been a substantial distance outboard of the Yilgarn Craton margin, as there is no evidence of a magmatic arc within the Albany–Fraser Orogen. The relatively quiescent period and apparent lack of magmatic activity from c.1600 to 1455 Ma indicates a change from active, rift-related extension, to a proto-oceanic rift, through to a passive-margin and adjoining marginal basin. This marked the onset of the second depositional cycle (Cycle 2), and initial formation of the Arid Basin. In contrast to the Barren Basin, the Arid Basin is dominated by c. 1455 to 1375 Ma detritus that does not correspond to any known source within the Albany–Fraser Orogen, signifying an external, but proximal, new source.This new source is interpreted to be an oceanic magmatic-arc — the c. 1410 Ma Loongana arc — within the Madura Province to the east of the Albany–Fraser Orogen. Soft collision and accretion of the Loongana oceanic magmaticarc at c. 1330 Ma took place after closure of the initial marginal basin via east-dipping subduction. In response to this accretion, Cycle 2 detritus from the oceanic magmatic-arc and its environs was fed into a foreland basin system that developed above a craton-vergent fold and thrust belt, producing a second phase of Arid Basin development. The accretion of the Loongana oceanic magmatic-arc is interpreted to have triggered the earliest magmatism of Stage I of the Albany–Fraser Orogeny at c. 1330 Ma. Detritus sourced from the Paleoproterozoic Biranup and Nornalup Zones, which constitutes the second-most abundant age component in the Arid Basin, was mixed with the younger foreland basin sediments. Thus, the Arid Basin evolved from a marginal ocean basin to a foreland basin, before it was intruded by granites of the widespread 1330–1280 Ma Recherche Supersuite and gabbros of the 1305–1290 Ma Fraser Zone. The two basin systems reflect a distinct change in tectonic regime from Paleoproterozoic rifting of the Yilgarn Craton, to the formation of a marginal basin that was subsequently closed during the Mesoproterozoic. The extensional structures produced during basin formation were inverted during orogen-wide, craton-vergent thrusting, which dominates the present-day crustal architecture.